COGNITIVE PROCESSES IN VERBALIZING AND REVERBALIZING RUSSIAN-UKRAINIAN WAR-TIME CONCEPTS - Oksana Molchko (Іноземна філологія)
Language as the source and instrument of human communication refl ects a number of aspects of a society’s life. The outbreak of the full-scale Russian-Ukrainian war in 2022 changed dramatically not only the life, but also the way Ukrainians verbalize the new war-time reality, with the media as its official recorder. The article identifi es some of the most frequently used new war-time lexical concepts with the models of metaconceptual derivation in its basis. The analysis suggests that affi xation, affixoscopy and affixocompounding are the models widely used in creating new war-time lexis. The cascade activation framing theory is applied in the article to explain why the bottom-up movement of a worldview, starting from the interpretation of reality by the public, results in new concepts of the war-time reality. The arguments are supported with war-time media corpus in Ukrainian and reverbalized English variants, proving the war’s impact on both languages.